Effect of Leadership Style and Leader Gender on Employee Performance - Firda Nuril Hanifah; Nuri Herachwati (Institute of Computer Science (IOCS), 2022)
Several previous research found that leadership style had a positive influent on employee performance, while the gender of the leader had no influent. Recently, there has been no research conducted to examine the effect of leadership style and leader gender on employee performance in a semi-military environment, where military leaders are often seen as having a distinctive leadership style. This research aims to determine whether the leadership style and gender of the leader influence the performance of employees in the Military Court III-12 Surabaya. This research was conducted through a quantitative approach. Respondents are the population of the Military Court III-12 Surabaya. The results of the study indicate that the leadership style and gender of the leader have a positive effect on employee performance.